Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557154
|View full text |Cite
|
Sign up to set email alerts
|

Sensing a live audience

Abstract: Psychophysiological measurement has the potential to play an important role in audience research. Currently, such research is still in its infancy and it usually involves collecting data in the laboratory, where during each experimental session one individual watches a video recording of a performance. We extend the experimental paradigm by simultaneously measuring Galvanic Skin Response (GSR) of a group of participants during a live performance. GSR data were synchronized with video footage of performers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 7 publications
1
37
1
Order By: Relevance
“…In our experiment, we had a non-engaging learning experience, and it is important to note that such situation (non-engaging experience) has not been reported before. Unlike the previous studies, the audience was engaged with a video (Dmochowski, Bezdek, Abelson, Johnson, Schumacher and Parra, 2014) or a comedy play (Wang, Geelhoed, Stenton and Cesar, 2014). However, during a non-engaging experience, we found that there were no such significant correlations existed between the two locations (surveys and GSR response), and there was no significant cross correlation between surveys and GSR readings.…”
Section: Correlationscontrasting
confidence: 76%
See 1 more Smart Citation
“…In our experiment, we had a non-engaging learning experience, and it is important to note that such situation (non-engaging experience) has not been reported before. Unlike the previous studies, the audience was engaged with a video (Dmochowski, Bezdek, Abelson, Johnson, Schumacher and Parra, 2014) or a comedy play (Wang, Geelhoed, Stenton and Cesar, 2014). However, during a non-engaging experience, we found that there were no such significant correlations existed between the two locations (surveys and GSR response), and there was no significant cross correlation between surveys and GSR readings.…”
Section: Correlationscontrasting
confidence: 76%
“…For instance, based on physiological signals, Ruan et al proposed a discriminant model to predict the fatigue state of players, so that the design of body-controlled games can be adapted and improved (Ruan, Chen, Sun and Chen, 2009). In addition, GSR sensors have also been studied for performing arts, Latuliper et al and Chen et al used both surveys and GSR sensors to investigate audience engagement at a lab and a field study respectively ( Latulipe, Carroll and Lottridge, 2011;Wang, Geelhoed, Stenton and Cesar, 2014).…”
Section: Gsr Sensorsmentioning
confidence: 99%
“…Two widely used dimensions for describing emotions are arousal (activation/excitement levels) and valence (positive or negative aspect of the emotion) [14], which are sensitive to short-term changes which can otherwise be difficult to detect. Galvanic skin response (GSR) and heart rate (HR) are commonly used measures of arousal and valence respectively [26,30]. GSR measures changes in skin conductance, and has been closely linked to measuring arousal and attention [30].…”
Section: Measuring Engagement and Viewer Experiencementioning
confidence: 99%
“…As such, no comparisons are made with mediated performances. The emphasis is on the very nature of the theatre experience, evaluating the pre-and post-performance experience, an area which we explored using Galvanic Skin Response audience sensing complementing self-report pre-and postperformance questionnaires [72].…”
Section: Quantitative Audience Evaluations Of Mediated Performancesmentioning
confidence: 99%